Vitamin D Deficiency and Its Association with Cirrhosis among Patients with Chronic Hepatitis C Infection: Vitamin D Deficiency and Association with Chronic Hepatitis C Infection - Nosher, Huma; Cheema, Tahira Murtaza; Iqbal, Iqra; Yousaf, Jahangir; Rizvi, Syed Mubashir Abbas; Amil, Javaria; Rehman, Aneeq Ur (Pakistan Journal of Health Sciences, 2026)
Vitamin D deficiency represents a common metabolic disturbance in chronic liver disorders, with a particularly high prevalence among individuals affected by chronic hepatitis C virus (HCV) infection. Evidence reported that progressive hepatic dysfunction can be linked to the waning levels of vitamin D; the information on South Asian populations is scarce. Objectives: To evaluate the association between deficient serum vitamin D levels and the presence of liver cirrhosis among individuals with HCV infection. Methods: The case-control study involved 162 chronic hepatitis C patients in the Department of Medicine, Kishwar Fazal Teaching Hospital, Lahore. Demographic, clinical, and laboratory parameters were taken. The level of vitamin D in serum was determined and categorized based on the severity. The statistical analysis was conducted using SPSS version 25.0 through suitable tests. Results: The study population had a vitamin D deficiency of 92.0%. Cases of severe vitamin D deficiency were found 30.2 higher in cirrhotic patients than in non-cirrhotic patients (30.2% vs. 14.0%). Severe vitamin D deficiency, female gender, and longer HCV infection were significantly related to cirrhosis. Extremely vitamin-D-deficient patients showed a high concentration of alanine aminotransferase and aspartate aminotransferase, elevated serum bilirubin, and decreased serum albumin, which is indicative of severe hepatic dysfunction. Conclusions: In chronic hepatitis C patients, vitamin D deficiency, especially the severe form, is highly correlated with cirrhosis and poor biochemical markers in the patients. These results justify the inclusion of regular screening of vitamin D status in the overall evaluation of patients with chronic HCV infection.